Evaluation of LoRaWAN Wireless Communication Protocol and its applicability in monitoring climate conditions - Oliveira, Lucas Restivo De [UNIFESP] (2019)
This work aimed to understand the methodology of implementation of the Internet of Things in Brazil through LoRa technology, which in recent years has shown enormous applicability for remote sensing in several countries around the world. The main characteristics of this type of long distance transmission, such as payload of up to 242 B, transmission rate of 27 kbps, range of up to 30 km, battery life of up to 10 years, node sensitivity of -136 dBm, bandwidth up to 500 kHz and operation in frequency-free spectrum (also known as Industrial Scientific and Medical, or, ISM), are directed to identify that there is an applicability of LoRa in the prevention of natural disasters, urban waste management and productivity in industries or rural areas. Thus, the main focus of this work was to provide a practical contribution to accessible and low cost hardware for the use of LoRa technology in Brazil, prototyping tests of reach, energy efficiency and technical feasibility for the national operation. It was possible to create a reusable programming library (LoBRa) for the hardware used that meets the transmission constraints in accordance with the regulations of the regulatory bodies.